Study about the knowledge and attitude of antenatal women on postnatal care and immunisation - Ali C. T., Basim; N., Fysal; S., Asha; C. V., Saleema (International Journal of Contemporary Pediatrics, 2019)
Background: Optimum postnatal care, exclusive breast feeding and vaccination are the most essential factors for the adequate growth and development of a child. Interventions to improve these can result in reduction in infant morbidity and mortality. The study was done to assess the knowledge level and attitude of antenatal mothers on postnatal care and immunisation. Methods: This is a cross-sectional descriptive study done in a private medical college in Kerala conducted during September 1 to 31st 2018. All pregnant ladies attending the medical college hospital for antenatal check-up during the study period and willing to participate were included. Data collection was done by interviewing the participants using pretested and edited questionnaire and analysed by applying proportions. Results: The awareness about postnatal care and breast feeding was good among participants while lacking in a few aspects. Majority of them had the right knowledge about pre-lacteal feeds, colostrum and timing of initiation of breast feeding. But there was a gap between the knowledge they possessed and what they practised when it comes to vaccination. Conclusions: There is a need to educate antenatal mothers about various aspects of vaccination and postnatal care.